Using anthesis date as a covariate to accurately assessing type II resistance to Fusarium head blight in field-grown bread wheat. (April 2021) - Franco, M.F.; Lori, G.A.; Cendoya, M.G.; Panelo, J.S.; Alonso, M.P.; Mirabella, N.E.; Malbrán, I.; Pontaroli, A.C.
Abstract: The identification of sources of resistance to Fusarium head blight (FHB) in bread wheat is key to the sustainable management of the disease. An accurate characterization of resistance is critical; however, the experimental designs commonly used disregard germplasm variability in anthesis date (moment of highest disease susceptibility). Here, an accurate methodology for assessing type II resistance to FHB in the field was developed. Individual spikes of 126 RILs were point-inoculated at their optimum moment. The effect of anthesis date and environmental conditions on the prediction of bread wheat lines' performance was established. Anthesis date explained 26% of the total phenotypic variation for Severity at 21 days post-inoculation (dpi). Including this factor in the model increased the accuracy of the best linear unbiased predictors through a reduction of the residual and genotype by environment interaction variances. In addition, the genotypic variance and heritability of FHB severity at 21 dpi were increased. In summary, including the anthesis date effect in the model lead to a more precise and objective characterization of the level of genetic type II resistance to FHB under field conditions. Highlights: Accurate assessment of resistance to Fusarium head blight in wheat is critical. Anthesis date variation between genetic materials leads to confounding effects. Considering anthesis date variation improves model prediction of type II resistance. Precise field phenotyping can improve QTL mapping and generation of resistant lines.